PERBEDAAN KONSUMSI ENERGI DAN ZAT GIZI MAKRO BERDASARKAN STATUS GIZI MAHASISWA FAKULTAS KESEHATAN MASYARAKAT UNIVERSITAS AIRLANGGA[Diff erence of Energy and Macronutrients Consumption Based on Nutritional Status among Student of Faculty of Public Health Universitas Airlangga ] - Mulki Auly Poetry; Triska Susila Nindya; Annas Buanasita (Media Gizi Indonesia, 2020)
Daily consumption could aff ect nutritional status. Overconsumption lead to overweight, while less consumption lead to underweight, that could happens to college student who started early adult phase. Aim of this research was to investigate the diff erence of energy and macronutrients consumption among students of Faculty of Public Health Universitas Airlangga. This was an observational analytic research using cross sectional design. Sample was randomly chosen as much as 72 students. Data was collected using height and weight anthropometric measurement to determine nutritional status and 3x 24h food recall. Statistical test used was one way Anova for energy and carbohydrate consumption variables and Kruskall Wallis test for protein and fat consumption variables. The result indicated prevalence of underweight, normal, and overweight students were 16.7%, 45.8%, and 37.5% consecutively. Overweight students tend to have higher average of energy and carbohydrate consumption. However, most of students consumed enough protein and fat. There were diff erences of energy (p=0.008) and carbohydrate consumption (p=0.047) based on nutritional status among students. Overweight students need to reduce energy and macronutrient consumption as an eff ort to achieve normal nutritional status.